Синтез и химические превращения 4-(N-морфолил)бензальдегида - Нуркенов, О.А.; Аринова, А.Е. (Изд-во КарГУ, 2011)
4-(N-морфолил)бензальдегидтің синтезі жəне кейбір химиялық түрлендірулері жүргізілді. Қысқатол- қынды сəулелендіру жағдайында 4-(N-морфолил)бензальдегидтің алыну реакциясы 30 мин ішінде ДМФА-те жүретіндігі анықталды. Үшкомпонентті конденсация тиомочевина, ацетосірке эфирі жəне 4-(N-морфолил)бензальдегид Биджинелли реакциясы бойынша конвекционды қыздыру жəне қысқа- толқынды сəулелендіру жағдайында этил-6-метил-4-(4-морфолинофенил)-2-тиоксо-1,2,3,4-тетрагид- ропиримидин карбоксилаттың алынуы зерттелді. Əрі қарай оның хлорсірке қышқылының метил эфи- рімен əрекеттесуі 3,5-дигидро-2H-тиазоло[3,2-a]пиримидинді алынуына əкеледі. Synthesis and some chemical transformations 4-(N-morpholyl)benzaldehyde were carried out. It was revealed that in conditions of the MW-irradiation reaction of reception 4-(N-morpholyl)benzaldehyde can be successfully carried out within 30 minutes in the DMF environment. The three-componental condensation tioareo, acetoacetic aster and 4-(N-morpholyl)benzaldehyde on reaction Biginelli in the conditions of classical heating and microwave irradiation with the formation of ethyl 6-methyl-4-(4-morpholinophenl)-2-thioxo-1,2,3,4- tetrahydropyrimidine-5-carboxylate were studied. The further interaction of the latter with the methyl ether chlorine acetic leads to the transformation into corresponding3,5-dihydro-2H-thiazole[3,2-a] pyrimidine.